POLITIK HUKUM PENGATURAN KEWENANGAN PENGELOLAAN WILAYAH PESISIR DAN PULAU-PULAU KECIL OLEH PEMERINTAH DAERAH DALAM KERANGKA NEGARA KESATUAN REPUBLIK INDONESIA - Dodi Jaya Wardana (Jurnal Justiciabelen, 2019)
Management of coastal areas and small islands by the regional government is essentially the implementation of regional autonomy that has been guaranteed by Article 18 paragraph (2) of the 1945 NRI Constitution. With the existence of regional autonomy, according to Article 18A of the 1945 NRI Constitution there is a relationship of authority in the management of coastal areas and small islands. For this reason, the authority of regional governments in managing coastal areas and small islands is an inseparable part of regional autonomy. Based on Article 50 of Law No. 1 of 2014 in conjunction with Article 18 of Law No. 32 of 2004, the provincial authorities ranging from 4 nautical miles to 12 nautical miles, while the regencies / cities have the authority ranging from 0 nautical miles to 4 nautical miles. However, since the enactment of Law no. 23 of 2014, specifically the provisions of Article 14 paragraph (1), management of coastal areas and small islands is only the authority of the Central and provincial governments. Provincial authorities start from 0 nautical miles to 12 nautical miles. Whereas regencies / cities no longer have authority in managing coastal areas and small islands.